Analysis of soybean crop data in the state of Mato Grosso, Brazil, in the period from 1990 to 2018 - Ribeiro, João Gabriel (2021)
Soybean production in Brazil plays a key role in supplying the domestic and foreign markets. Brazil ranks first in world soybean production, driven mainly by the state of Mato Grosso, which leads the soybean production complex in the country. In this context, data of soybean grain production in thousand tons, value of soybean grain production in thousand reais and the value of soybean derivatives in thousand reais for that state, in the period from 1990 to 2018, were collected from the Brazilian Institute of Geography and Statistics (IBGE). Then, univariate imputation techniques via cubic spline interpolation were applied to missing data from 46 municipalities in the state, for the three variables, in order to complete this data set, and reveal estimates for the same variables. Finally, there were applications of cluster analysis, for the complete data of the 141 municipalities in the state from 1990 to 2018, on the same variables. From the 5, 5 and 4 staggered groups created and statistically validated for the variables of soybean production in thousand tons, soybean production value in thousand reais and value of soybean production derivatives in thousand reais, a zoning of soybean production activity was generated out in the state of Mato Grosso during this period, and this productive overview of the crop can be a contribution to the state in developing public policies in this segment as well as an attraction of investors in the state interested in this culture.